Majejaitan Activity and High Serum BDNF Levels as Protective Factors Against Cognitive Impairment in the Elderly - Komang Indah Permata Dewi; I Putu Eka Widyadharma; Nila Wahyuni; Wayan Putu Sutirta Yasa; I Dewa Ayu Inten Dwi Primayanti; Ni Luh Gede Yoni Komalasari (Green Publisher Indonesia, 2025)
The aging process in the elderly affects not only physical capabilities but also cognitive function. Cognitive impairment in older adults is thought to be associated with physical activity and neurotrophic factors, particularly the serum level of Brain-Derived Neurotrophic Factor (BDNF). Majejaitan—a traditional form of activity involving fine motor coordination and repetitive hand movements—is hypothesized to exert a protective effect against cognitive impairment by increasing serum BDNF levels. This study aimed to examine the role of Majejaitan activity and elevated serum BDNF levels as potential protective factors against cognitive impairment in elderly individuals. An observational case-control study was conducted from November 2024 to January 2025 at the East Denpasar 1 Primary Health Care Center. The participants were women aged 50–60 years, divided equally into two groups: a case group (with cognitive impairment) and a control group (without cognitive impairment), each consisting of 19 participants. Cognitive impairment was assessed using the Indonesian version of the Montreal Cognitive Assessment (MoCA-Ina), with scores below 26 indicating impairment. Majejaitan activity was defined as performing the activity at least three times per week for 30–60 minutes, and participants were classified as either active or inactive. Serum BDNF levels were measured using a sandwich-type ELISA with the Human BDNF ELISA Kit (BT LAB) and were categorized as high or not high based on receiver operating characteristic (ROC) curve analysis.